Tuturan Masyarakat Sumatera Selatan “Wong Rumah” dalam Perspektif Budaya Islam Melayu - Mardinana Mardinana; Helen Sabera Adib; Chici Rima Putri Pratama (An Nisa'a, 2017)
This paper begins with the thought and assumption that the speech "wong rumah" can form the effect of kinship on one hand and the effect of subordinating to women in South Sumatra. Initial Observation results found that the language "wong rumah" is a colloquial language that has been grounded in the South Sumatra region in analyzing the explanation of wife's news to friends. Between the "wong rumah" and gender in this study are two sides that have similar implications, namely obtaining a common ground of question, "is the language of "wong rumah" a representation of the gender subordination of the Palembang community? Mapping the meaning of "wong rumah" for every society is different. It is actually in addition based on the customs, culture and the role of someone who is attached to a community. From the results of research using quantitative methods, it can be concluded that the meaning of "wong rumah" is a symbol of one's position or strata in the community